Factors influencing institutionalization of health technology assessment in Kenya - Rahab Mbau; Anna Vassall; Lucy Gilson; Edwine Barasa (BMC, 2023)
Abstract Background There is a global interest in institutionalizing health technology assessment (HTA) as an approach for explicit healthcare priority-setting. Institutionalization of HTA refers to the process of conducting and utilizing HTA as a normative practice for guiding resource allocation decisions within the health system. In this study, we aimed to examine the factors that were influencing institutionalization of HTA in Kenya. Methods We conducted a qualitative case study using document reviews and in-depth interviews with 30 participants involved in the HTA institutionalization process in Kenya. We used a thematic approach to analyze the data. Results We found that institutionalization of HTA in Kenya was being supported by factors such as establishment of organizational structures for HTA; availability of legal frameworks and policies on HTA; increasing availability of awareness creation and capacity-building initiatives for HTA; policymakers' interests in universal health coverage and optimal allocation of resources; technocrats' interests in evidence-based processes; presence of international collaboration for HTA; and lastly, involvement of bilateral agencies. On the other hand, institutionalization of HTA was being undermined by limited availability of skilled human resources, financial resources, and information resources for HTA; lack of HTA guidelines and decision-making frameworks; limited HTA awareness among subnational stakeholders; and industries' interests in safeguarding their revenue. Conclusions Kenya's Ministry of Health can facilitate institutionalization of HTA by adopting a systemic approach that involves: - (a) introducing long-term capacity-building initiatives to strengthen human and technical capacity for HTA; (b) earmarking national health budgets to ensure adequate financial resources for HTA; (c) introducing a cost database and promoting timely data collection to ensure availability of data for HTA; (d) developing context specific HTA guidelines and decision-making frameworks to facilitate HTA processes; (e) conducting deeper advocacy to strengthen HTA awareness among subnational stakeholders; and (f) managing stakeholders' interests to minimize opposition to institutionalization of HTA.